Combustion and emission characteristics of a diesel-powered generator running with N-butanol/coffee ground pyrolysis oil/diesel blended fuel. (1st September 2020) - Lee, Seokhwan; Woo, Sang Hee; Kim, Yongrae; Choi, Young; Kang, Kernyong
Abstract: Demand for alternative energy is steadily increasing due to the depletion of fossil fuels. Converting biomass into alternative fuels has been proposed as a potential solution. Biofuel obtained from biomass through a pyrolysis process is called pyrolysis oil (PO). Because PO is difficult to use directly in conventional engines due to its inadequate fuel properties, various methods have been proposed to improve the fuel properties. Among them, using an alcohol fuel as an organic solvent has been proposed to mix PO with diesel to significantly improve fuel properties. In this study, a blend of diesel, n-butanol, and coffee ground pyrolysis oil (CGO) was applied to a diesel-powered generator. The experimental results showed that stable combustion was possible regardless of fuel type. Although, the fuel consumption rate of the blended fuels was about 20% higher than that of diesel, the efficiencies of all of the test fuels were comparable. NOx emissions decreased about 15–30% for the blended fuels than diesel due to high evaporating latent heat of n-butanol and water content of CGO. The blended fuels showed 70–90% lower PM mass emissions than diesel owing to the oxygen in n-butanol and CGO. Highlights: The applicability of coffee ground pyrolysis oil in a diesel generator was studied. The blended fuels consist of n-butanol, coffee ground pyrolysis oil, and diesel. Stable engine combustion was guaranteed regardless of fuel type. NOx emissions decreased about 15–30% for the blended fuels than diesel. PM mass emissions of the blended fuels were lower up to 90% than that of diesel.